Faktor-faktor yang mempengaruhi penggunaan alat pelindung diri (apd) dalam pelayanan kebidanan di praktek mandiri bidan (pmb) pada masa pandemi covid-19 : Factors influencing the use of personal protective equipment (ppe) in midwifery services, in midwife independent practice (pmb) during the covid-19 pandemic - Adnyani, Sukma (Bali Medika Jurnal, 2021)
Midwives are part of the frontline health workers who are in direct contact with clients and have a risk of being exposed to Covid-19. To protect oneself during direct contact with clients, it is mandatory to adhere to infection prevention and control practices, which include administrative, environmental and engineering controls as well as proper use of Personal Protective Equipment (PPE). The purpose of this study was to analyze the factors that influence the behavior of midwives in the use of appropriate PPE in midwifery services during the Covid-19 pandemic and the adaptation of new habits. The design of this study was cross-sectional analytic. The subject of the study was the Pomegranate Midwife in Denpasar City who had an Independent Midwife Practice who continued to provide services during the Covid-19 pandemic with a sample of 63 people according to the inclusion criteria. The results showed that there was a significant relationship between age (p=0.012), work experience (p= 0.011), attitude (p= 0.01) and knowledge (p= 0.014) with behavior in the use of Personal Protective Equipment (PPE). appropriate level in providing midwifery services during the Covid-19 pandemic. So that to maintain good service quality, midwives in providing services continue to apply health protocols, maintain service quality by maintaining knowledge, and use appropriate levels in midwifery services.